Human and Organisational Factors Practices and Strategies for a Changing World - Journé, Benoît; Laroche, Hervé; Bieder, Corinne; Gilbert, Claude (SpringerBriefs in Applied Sciences and Technology, 2020)
This open access book addresses several questions regarding the implementation of human and organisational factors (HOF) so that recent improvements in industrial safety can be built upon. It addresses sources of frustration in senior management with high expectations of operational recommendations and disquiet on the part of HOF specialists struggling to have an impact on high-level decision making. The brief explores these issues with an emphasis on examples and lessons learned based on the experience of its authors, who come from different academic disciplines and various industrial sectors such as oil and gas, energy and transportation. It then offers some ways forward for a better consideration of HOF in hazardous companies with a view of promoting safety and facing challenges in a rapidly changing world.